Foreword to the Special Issue of ESCO 2022 Conference. - Galán-García, José Luis; Aguilera-Venegas, Gabriel; Galán-García, María Ángeles (Springer, 2023)
Foreword to the special issue with selected papers from the 8th edition of the European Seminar on COmputing (ESCO) Conference, held in Pilsen (Czech Republic) on June 13th to 17th. ESCO is a successful series of interdisciplinary international conferences. It promotes modern technologies and practices in scientific computing and visualization, and strengthens the interaction between researchers and practitioners in various areas of computational engineering, sciences and education. The conference had a hybrid format: in person and online participations. In this 8th edition of ESCO, there were over 200 participants from more than 30 countries all over the world. Five keynote lectures and 182 talks and posters were presented during the conference.
https://openpolicyfinder.jisc.ac.uk/id/publication/14486 (12 meses de embargo a partir de la fecha de publicación)
Keywords: Matemáticas - Congresos; Editorial; Special Issue